On an inverse source problem for the Biot equations in electro-seismic imaging*The research of YG was supported in part by NSFC grant 11871140, 11571065, 11671071, JJKH20180006KJ, JLSTDP20190201154JC, 20160520094JH and FRFCU2412017FZ005. The research of YY was partly supported by the NSF Grant DMS-1715178, the AMS-Simons travel grant, and the start-up fund from the Michigan State University. (21st August 2019) - Gao, Yixian; Li, Peijun; Yang, Yang
Abstract: Electro-seismic imaging is a novel hybrid imaging modality in geophysical exploration where electromagnetic wave and seismic wave are coupled in porous medium. This paper concerns with an inverse source problem for the Biot's equations arising in electro-seismic imaging. Using the time reversal method, we derive an explicit reconstruction formula, which immediately gives the uniqueness and stability of the reconstructed source.